Backup Link Reviewed Layer Distribution Method Using Virtual Router Redundancy Protocol (VRRP) - Nurhazmi Hawari; Iskandar Fitri; Andri Aningsih (Jurnal Teknik Informatika C.I.T Medicom, 2019)
Internet networks run 24 hours a day and must provide a stable performance and reliable, the networks of local SMK Tridharma Budhidaya there is only one router and when the router such disturbances then the internet at the school disrupted and therefore to prevent the internet is not happen down the proposed use by implanting method Backup Router Virtual Router redundancy Protocol (VRRP) After that is done four stages of testing and Througputh Loss Package. Software testing is done using Wireshark results in Loss Package testing get 10, 20, 30, 40, 50, 60 Minutes yield value of 0.43%, 0.21%, 0.20%, 0.10%, 0.8% , 0.10% Loss Package Referring TIPHON below 3% is quite good and the testing Througputh for 10, 20, 30, 40, 50, 60 minutes, producing a value 275Bit / s, 280 Bit / s, 282 bits / s, 282 bits / s, 279 bits / s, 278 bits / s referring to standardize TIPHON that the average yield testing Througputh 279 Bit / s is said to be very good. with this result VRRP method is able to provide solutions when the Main Router encountered a problem and still maintain good quality of the network.